Evaluating the Java Native Interface (JNI): Data Types and Strings - Sotiriadis, Stelios; Omosebi, Oladotun; Ayapbergenova, Assem; Saparkhojayev, Nurbek P (International journal of distributed systems and technologies, 2018)
This article describes how the java native interface (JNI) is a powerful feature of the java platform that started to draw attention in the latter years as an efficient programming framework for building and delivering innovative technological applications based on disruptive technologies such as mobile, Internet of Things and embedded systems. Developers use it to incorporate native code written in programming languages such as C, C++, python etc., into java. JNI is particularly useful when java applications need to access existing native libraries or code blocks written in other languages to increase performance, avoid recoding and expand interoperability between programming languages for processes that reside in the same process. This article aims to explore JNI features and to discover fundamental operations of the Java programming language, such as arrays, objects, classes, threads and exception handling, and to illustrate these by using various algorithms and code samples.